(untitled) (Development Service Industry Management, 2023)
The article considers the essence of the term "project" and determines the following approaches to its understanding: a set of actions or activities (changes), a set of interrelated measures, a set of documents, procedures and all necessary measures to create an innovative product, a set of processes and tasks in order to achieve the goal. The author’s definition of the concept of "project" is provided. In particular, the “project" should be understood as a set of interrelated measures and steps to achieve the goals through changes in object of management, taking into account resource constraints. The main features that determine the essence of the project and make it unique, were underlined, in particular: goals and objectives, limitations, resources, time frames, complexity and risks. The relevance of the use of agile management in the project activities of the enterprise is substantiated. The article describes agile methodologies (eXtreme Programming (XP), Scrum, Acceptance Test-Driven Development (ATDD), Dynamic Systems Development Method (DSDM), Lean Software Development, Test Driven Development (TDD). It is specified that Agile-project management (flexible project management) is amethodology stresses the importance of adaptability to change. with main idea to respond flexibly to changes in requirements, circumstances and assumptions while developing a project. In the Agile methodology, the project cycle is divided into iterative stages, which typically include the following main phases: planning, execution, verification/evaluation, review and retrospective. The primary elements of the Agile project are identified and characterized: product backlog, sprints, sprint backlog, daily stand-ups, sprint review, and retrospectives.